2016
DOI: 10.1039/c6mb00568c
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the cross-talking of human competitive endogenous RNAs in K562 chronic myelogenous leukemia cell line

Abstract: Chronic myelogenous leukemia (CML) is a myeloproliferative disorder characterized by increased proliferation or abnormal accumulation of granulocytic cell line without the depletion of their capacity to differentiate. A reciprocal chromosomal translocation proceeding to the 'Philadelphia chromosome', involving the ABL proto-oncogene and BCR gene residing on Chromosome 9 and 22 respectively, is observed to be attributed to CML pathogenesis. Recent studies have been unraveling the crucial role of genomic 'dark m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…He et al found that SNHG5 promoted imatinib resistance in CML via acting as a ceRNA against miR-205-5p [7]. Sen et al constructed a ceRNA network for the CML cell line, and the top ranked significant functional modules in the ceRNA network displayed cancer associated attributes and revealed putative regulators in CML pathogenesis [8].…”
Section: Introductionmentioning
confidence: 99%
“…He et al found that SNHG5 promoted imatinib resistance in CML via acting as a ceRNA against miR-205-5p [7]. Sen et al constructed a ceRNA network for the CML cell line, and the top ranked significant functional modules in the ceRNA network displayed cancer associated attributes and revealed putative regulators in CML pathogenesis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, competing endogenous RNAs (ceRNAs) participate in microRNA (miRNA)-dependent crosstalk and contribute to the complexity of gene regulation, and may aid in the understanding of disease pathobiology ( 9 ). lncRNAs regulate the expression of neighboring coding genes through various mechanisms and may function as ceRNAs to modulate the derepression of miRNA targets ( 10 ). In recent years, the roles of lncRNAs in several diseases and cancers have been investigated ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%